Intraocular pressure and ocular biomechanical parameters vary between generations of the ocular response analyzer in healthy and ectatic eyes - Phillip T. Yuhas; Maddison M. Fortman; Michael Nye; Ashraf M. Mahmoud; Cynthia J. Roberts; Cynthia J. Roberts (Frontiers in Medicine)
IntroductionThis study evaluated the agreement between a third-generation (G3) ocular response analyzer (ORA) and a first-generation (G1) ORA, and tested the ability of the keratoconus match index (KMI) to identify keratoconus.MethodsHealthy participants (n = 149 eyes) and participants with keratoconus (n = 78 eyes) were enrolled for this study. Four measurements were taken bilaterally using the G1 and G3 ORA. Goldmann-correlated intraocular pressure (IOPg), corneal-compensated IOP (IOPcc), corneal hysteresis (CH), waveform score, KMI, and waveform parameters area under the first applanation peak (p1area), area under the second applanation peak (p2area), width of the first applanation peak (w1), width of the second applanation peak (w2), height of the first applanation peak (h1), and height of the second applanation peak (h2) were recorded from the measurement with the highest waveform score in the left eye. Paired t-tests or Wilcoxon signed-rank tests were used to assess agreement between the devices, and receiver-operating characteristic curves determined the ability of KMI to identify eyes with keratoconus.ResultsThere was no difference in IOPcc or IOPg between the devices in both cohorts. CH was significantly greater for the G3 than for the G1 in healthy participants but not in keratoconus participants. For both cohorts, measurements of waveform score, KMI, p1area, p2area, w2, h1, and h2 were greater for the G3 than for the G1. Only w1 was smaller for the G3 than for the G1. There was no difference in the ability of KMI to differentiate ectatic from healthy eyes between the devices.DiscussionAlthough the G1 and G3 can identify keratoconus using KMI, there is meaningful variation between them in IOP and biomechanical outcome parameters. Thus, clinicians and researchers should compare results between the devices with caution and should state which generation produced the data.